Optimizing Distribution Transformer Ratings in the Presence of Electric Vehicle Charging and Renewable Energy Integration - Argade, Sachin; Vashikar, Vishal; Anantwar, Harsha; Chavan, Sudarshan L. (Recent Advances in Electrical & Electronic Engineering, 2025)
<span class=
Keywords: energy storage